Dopant and excitation wavelength dependent color-tunable white light-emitting Ln3+:Y2WO6 materials (Ln3+ = Sm, Eu, Tb, Dy)1. Issue 33 (7th September 2015) - Van Deun, Rik; Ndagsi, Dorine; Liu, Jing; Van Driessche, Isabel; Van Hecke, Kristof; Kaczmarek, Anna M.
<x xml:space="preserve">Abstract</x> Color-tunable Y2WO6 microstructures doped or co-doped with Sm3+, Eu3+, Tb3+, and Dy3+ were synthesized in the presence of glycerol both as a solvent and a structure directing agent for obtaining white light emitting materials.